Long Distance Marriage to Keep Sakinah's Family Established - Mahfudz, Muhammad Sahal (Al Mashaadir : Jurnal Ilmu Syariah, 2023)
The family is created as a result of a marriage performed by a man and woman who have fulfilled the requirements. The sakinah family is everyone's dream. But in reality creating a sakinah family is so difficult, one of which is for families with different places to live. Distance and time create problems for wife married couples because they cannot meet physically. It creates an obstacle for husband and wife to exercise their rights and obligations. Many married couples in running relationships experience problems, both couples who live together or couples who live differently. Couples who live differently, usually due to work, economic, and educational factors. As for ways that can keep the family well established, then the couple must do openness, mutual trust, and also communications that the family is maintained well and peacefully.  This research uses a mixture of qualitative and quantitative methods.  Then in the analysis the researcher uses the theory of social construction. In the results of this study there are several ways and solutions for family life in different places of residence, namely: 1) understanding and understanding marriage, 2) confidence and openness, 3) good communication between families, 4) commitment to the couple, and 5) deliberation and consensus before marriage.   The results of this study are expected to have an impact on families of different places of residence, in order to remain sakinah families.